Finite Element Analysis of Material Handling System Components - Aarbaz Mutwalli; Jamil Dabir; Maruti Khot (International Journal of Engineering and Management Research, 2023)
In any industry, a transport system is always required. Lifting and moving heavy goods over great distances has traditionally been done by workers. This may be economically beneficial to the employer but certainly is counter-productive in a way, considering the time required for the displacement as well as the health risks associated due to prolonged work. This work focuses on the design and analysis of an overhead Monorail system. The design analysis of overhead monorail crane with a single beam has been proposed. In this paper the design analysis of hoist track, support column and hook has been done and study of results of finite element analysis of crane components with 1 ton capacity and 27 m span length has been conducted. The optimum design was selected using various materials handling system method and further tested for its structural performance using finite element analysis. The 3D model prepared and finite element analysis was also used to confirm the structural integrity of the new concept design.